(untitled) (Journal of Philosophy Culture and Political Science, 2020)
It is shown that at present the category of pseudoscientific requires consistent philosophical reflection. This is determined, first of all, by the need to rethink the disciplinary structure of science, which has ceased to satisfy the current needs of the development of civilization. On the agenda is the thesis on the New Enlightenment, promoted by the Club of Rome, as well as the thesis on the renaissance of philosophical knowledge aimed at the systematic elimination of interdisciplinary barriers. In such conditions, the criteria of scientific and pseudoscience developed within the framework of individual particular sciences cease to meet the needs of the further development of civilization; a higher level of understanding of the problem is needed – philosophical. It is shown that at the present stage, scientific work, which carries a significant baggage of ideas, is gaining importance, while ordinary publications made in the context of the ritualization of scientific research should fade into the background and be treated as pseudoscientific. The proposed interpretation of the opposition “scientific – pseudoscientific” is considered by comparing the ideas contained in the monograph by O.O. Suleimenova “Az and I”, with some modern studies that do not contain any new ideas and do not represent real value, but fully responding the existing scientific and bureaucratic canons. Key words: pseudoscience, renaissance of philosophical knowledge, New Enlightenment, Club of Rome, disciplinary structure of science, interdisciplinary barriers.